Monitoring the effect of football match congestion on hamstring strength and lower limb flexibility: Potential for secondary injury prevention? - Wollin, M.; Thorborg, K.; Pizzari, T. (Physical Therapy in Sport, 2018)
Objectives: To investigate the effect of competitive football match congestion on hamstring strength and lower limb flexibility. Design: Repeated measures. Setting: Elite male youth football. Participants: Fifteen male elite youth football players from the national football association centre of excellence were included (age = 15.81 ±0.65 years, height = 171.95 ±6.89 cm, weight = 65.93 ±7.53 kg). Main outcome measures: Hamstring strength and pain, ankle dorsiflexion, hip extension, knee extension and flexion range of motion. Results: Hamstring strength was highest at baseline and significantly reduced at 24 (p = 0.001, mean difference -0.19 Nm/Kg, CI95 -0.28, -0.1) and 48 h post-match 1 (p = 0.002, mean difference -0.16 Nm/Kg, CI95 -0.25, -0.07). Strength recovered by match day 2 before significantly reducing again 24 h post-match 2 (p = 0.012, mean difference -0.17 Nm/Kg, CI95 -0.29, -0.04). Pain was lowest at baseline and increased in the post-match periods (p < 0.05) with standardised effect sizes ranging from 0.07 to 0.42. Passive knee flexion range decreased post-match (p < 0.01) with mean differences of 1.5°-2.7°. The other flexibility measures remained unaffected by match play. Conclusion: Isometric hamstring strength and pain can be considered for inclusion in-season to monitor player's post-match hamstring recovery characteristics during congested match fixtures.